(untitled) (Community Based Medical Journal, 2022)
A prospective, observational study was conducted in the Department of Obstetrics & Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between July 2008 and January 2009 to compare position and attachment of the babies during breastfeeding before and after counselling the mothers. Our study samples include 100 healthy mothers and 100 term healthy babies. Initially, all the mothers and babies were observed for their position and attachment during breastfeeding within 24 hours of the delivery and documented in a standard data sheet. Then the mothers were shown the wall chart of nursing mothers and breastfeeding manual and taught practically by the investigators. Mothers were requested to come after 15 days for follow-up visit so that they become physically fit by that time and improve their skills. At follow-up visit, documentation of the position and attachment during breastfeeding was done in the data sheet. Comparison of each of the components of positioning and attachment was done with first observation (i.e., within 24 hours of the birth of the baby) and follow-up observation (i.e., after 15 days). The mean age of the mothers was 29.40±4.71 years. In all components of the position and attachment of the babies, the difference between before and after counselling the mothers was statistically significant (P<0.05). Similarly, in all signs of effective sucking, the difference was also statistically significant between before and after counselling (P<0.05) except for the sign of oxytocin reflex noticed by the mother (P>0.05). CBMJ 2022 July: vol. 11 no. 02 P: 102-107